Subjective parameters markedly limit the referral of transplantation candidates to liver transplant centres. (21st December 2015) - Vidal‐Trécan, Gwenaëlle; Kone, Victoria; Pilette, Christophe; Nousbaum, Jean‐Baptiste; Doll, Jacques; Buffet, Catherine; Eugene, Claude; Podevin, Philippe; Boutet, Olivier; Puyeo, Jacques; Conti, Filomena; Calmus, Yvon
Abstract: Background & Aims: Equality of access to organ transplantation is a mandatory public health requirement. Referral from a local to a university hospital and then registration on the national waiting list are the two key steps enabling access to liver transplantation (LT). Although the latter procedure is well defined using the Model for End‐stage Liver Disease score that improves equality of access, the former is mostly reliant on the practices of referring physicians. The aim of this study was to clarify the factors determining this initial step. Methods: This observational study included consecutive inpatients with cirrhosis of whatever origin in a cohort constituted between 2003 and 2008, using medical records and structured questionnaires concerning patient characteristics and the opinions of hospital clinicians. Candidates for LT were defined in line with these opinions. Results: Four hundred and thirty‐three patients, mostly affected by alcoholic cirrhosis, were included, 21.0% of whom were considered to be candidates for LT. Factors independently associated with their candidature were: physician empathy [odds ratio (OR) = 10.8; 95% CI: 4.0–29.5], adherence to treatment (OR = 16.6; 95% CI: 3.7–75.2), geographical area (OR = 6.8; 95% CI: 2.2–21.3) and the patient's physiological age (OR = 2.3; 95% CI: 1.1–4.7). Conclusions: Several subjective markers restrict the referral of patients from local hospitals to liver transplant centres. Their advancement to this second step is thus markedly weakened by initial subjectivity. The development of objective guidelines for local hospital physicians to assist them with their initial decision‐making on LT is now necessary.